From Il materiale e l’immaginario to La vita immaginata: Perspectives on the Periodisation of Contemporary Poetry (Configurazioni. Research on contemporary poetry, 2023)
A diachronic analysis of periodization and canon data in some school anthologies of the last forty years - from Ceserani and De Federicis’s Il materiale e l’immaginario to Prandi’s La vita immaginata - brings along a history of the didactics of contemporary poetry and clarifies some of its epistemological facets. The first part of the contribution is dedicated to this reconnaissance. In the second part an orientation map is proposed, for the use of teachers, which can be useful for translating into teaching practice a still varied and fluid framework.
Keywords: contemporary poetry; poetic canon; periodization; teaching of poetry; school anthologies